The Relationship Between Online Game Addiction And Sleep Quality In Grade IX Junior High School Students - Nurannisa, Isma Ayu; Mantu, Melani Rakhmi (Media Informasi, 2024)
Online game addiction is one of problems due to technology advancement such as digital devices and internet. Online games can be played indefinitely which lead addiction with symptoms such as not capable to control the desire of play game, having higher priority in playing game than other activities, and still choosing to play game even though knowing that there are negative effects. Online game addiction affects sleep duration that can lead to sleep quality problems. This research aims to investigate the association between online game addiction and sleep quality of 9th grade male students at SMPN 1 Kota Serang on January until March 2022. This research was conducted by using the analytic design with a cross sectional approach. Sampling used a consecutive sampling technique. The data was collected by using validated in Indonesian of Indonesia Online Game Addiction Questionnaire and Pittsburgh Sleep Quality Index and analyzed with chi square test in SPSS (Statistical Product and Service Solutions) version 22. The total sample obtained of 148 respondents and there is a significant association between online game addiction and sleep quality with p-value 0,000. This research concluded that online game addiction affects sleep quality.